A Tumor‐Organoid‐Based Precision Medicine Platform for the Prediction of Drug Sensitivity of Colorectal Cancer. Issue 12 (4th September 2022) - Wang, Xingyue; Lu, Xiaohuan; Cai, Bo; Li, Xiaoqiong; Zou, Danyi; Lei, Shijun; Xu, Luming; Wang, Guobin; Wang, Lin; Wang, Zheng
Abstract: Investigation of clinical actionable targets is crucial for the individual treatment of patients with advanced colorectal cancer (CRC). A complete platform integrating the molecular profiling and prediction of drug reactivity is currently scarce. An integrated precision medicine approach which combines high‐throughput sequencing platform with microfluidic organoid drug testing system is established. Capture sequencing identifies 6 drug targetable genes and 13 candidate drugs for a stage III colorectal cancer patient. The drug sensitivity is confirmed by using patient‐derived organoids (PDOs) model and microfluidic drug testing system. With this integrated precision medicine approach, the optimal drugs including Afatinib, Dacomitinib, and Osimertinib are successfully identified. The platform provides a practical method to guide the clinical therapies for colorectal cancer patients. Abstract : A platform is developed which integrates organoids model and microfluidic system. By using the platform, a patient's in vitro response to candidate drugs is predicted. In addition, this approach proves to be promising for high throughput drug screening. This work provides a novel insight to precision medicine for CRC patients, especially those who fail routine treatment.